Method for producing high-purity nano calcium carbonate by using CO2 mineralized carbide slag

Through the process method of combining low-temperature calcination, magnetic separation and settlement, SiO2 impurities are removed by combining CaSO4 particles, and crystal-form regulators are used to improve the purity and whiteness of nano calcium carbonate, which solves the high energy consumption when preparing nano calcium carbonate in calcium carbide slag. and the problem of difficulty in removing impurities, achieving high purity and high efficiency production.

CN119430256APending Publication Date: 2025-02-14SHANXI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411481423.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art has problems such as high energy consumption, difficulty in removing SiO2 impurities, and uneven product purity and morphology when preparing nano calcium carbonate in calcium carbide slag.

Method used

Using a combination of low-temperature calcination, magnetic separation and sedimentation, the SiO2 impurities are removed by adding CaSO4 or CaSO4·1/2H2O particles, and sodium tripolyphosphate and EDTA are used as crystal form regulators in the mineralization reaction to improve the product purity and whiteness.

Benefits of technology

It greatly reduces process energy consumption, effectively removes SiO2 impurities, and improves the purity and whiteness of nano calcium carbonate. The product purity reaches 95.00%-99.60%, and the whiteness reaches 95.0-98.0.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430256A_ABST
    Figure CN119430256A_ABST
Patent Text Reader

Abstract

The invention aims to provide a method for producing high-purity nano calcium carbonate by using CO2 mineralized carbide slag, and belongs to the technical field of production of high-purity nano calcium carbonate, the working process of the method comprises the following steps: calcining the carbide slag at low temperature, adding water into the calcined carbide slag for size mixing, then adding small-particle-size CaSO4 or CaSO4. 1 / 2H2O into the size, and stirring to obtain the high-purity nano calcium carbonate. The method comprises the following steps: adding calcium carbide slag slurry into a reactor, standing, carrying out wet magnetic separation and sedimentation on the slurry, introducing a settled carbide slag slurry solid deposition upper layer and a supernatant into a carbonization reactor, adding a crystal form regulating agent, introducing CO2 gas, carrying out a mineralization reaction, and filtering, drying and grinding the mineralized slurry to obtain a high-purity nano calcium carbonate product. The method has the characteristics of being simple in process, obvious in energy-saving advantage, high in practicability and easy to operate and use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of production of high-purity nano calcium carbonate, and specifically relates to a method for producing high-purity nano calcium carbonate by using CO 2 A method for producing high-purity nano-calcium carbonate from mineralized carbide slag. Background Art

[0002] Carbide slag is a byproduct left after acetylene is produced by the reaction of carbide and water. Its main component is calcium hydroxide, and it also contains impurities such as coke, ferrosilicon, and aluminum silicon. In the process of converting carbide into acetylene gas, about 1.2 tons of dry carbide slag is produced for every ton of carbide. The large amount of carbide slag has already had a serious impact on the ecological environment.

[0003] CO 2 As one of the greenhouse gases, it has an important impact on global warming. 2 Transforming it into valuable products can not only promote the innovation of technology and products, but also effectively alleviate the current CO 2 The content of calcium hydroxide in carbide slag is about 80%. Carbide slag has a high content of Ca(OH) 2 content and water solubility, with mineralized CO 2 The reaction conditions are simple, the reaction speed is fast, and CO 2 It has the advantages of strong capture capacity and high purity of prepared calcium carbonate. 2 Mineralization can permanently store CO in the form of carbonate minerals 2 , and produce high value-added products.

[0004] CO 2 The general steps for preparing nano calcium carbonate from indirect mineralization of carbide slag include two main processes: leaching and carbonization. First, by using NH 4 Extract Ca from carbide slag using leaching agents such as Cl 2+ ions, and then CO was introduced into the calcium solution obtained by leaching. 2 Carbonization reaction is carried out to produce nano-scale calcium carbonate. However, this method requires the use of ammonia water, and the waste residue and waste liquid generated during the reaction are difficult to handle. 2 Direct mineralization of carbide slag to prepare nano calcium carbonate first uses screening, high temperature calcination, cyclone, hydrocyclone and other methods to remove impurities, and then conducts mineralization reaction to prepare nano calcium carbonate. This method not only has high energy consumption, but also screening, cyclone and other methods cannot completely remove the impurity SiO in carbide slag. 2 , which has a great impact on the application of its products.

[0005] In addition, the current carbide slag mineralization CO 2The co-production of nano calcium carbonate has some problems such as uneven crystal form and morphology, difficulty in regulation, and low product purity. Therefore, a new process needs to be developed to solve the high energy consumption and SiO 2 It is difficult to remove and a series of problems. 4 or CaSO 4 1 / 2H 2 O characteristics, that is, adding small-sized CaSO 4 or CaSO 4 1 / 2H 2 O particles, small-sized CaSO 4 The particles will dissolve in the slurry, while the larger CaSO 4 These particles will recrystallize, preferentially in the SiO 2 The surface grows and wraps it to form a whole flocculent body, and during the sinking process, SiO 2 The CaSO 4 The density is about 2.96 g / cm 3 , Ca(OH) 2 Density is about 2.24g / cm 3 The density difference between the two is large, so this characteristic can be combined with gravity sedimentation method to remove SiO2 in carbide slag. 2 Impurities. Summary of the invention

[0006] In view of the above problems, the present invention provides a method for utilizing CO 2 The method of producing high-purity nano calcium carbonate from mineralized carbide slag adopts a process method combining low-temperature calcination, magnetic separation and sedimentation. The process adopts low-temperature calcination to greatly reduce the overall energy consumption of the process, and at the same time adopts a method combining mineral characteristics with gravity sedimentation to remove impurities SiO 2 In addition, additives are added to adjust the crystal form of the product to improve the purity and whiteness of the product.

[0007] The present invention adopts the following technical solution: A method of utilizing CO 2 The method for producing high-purity nano calcium carbonate from mineralized carbide slag comprises the following steps: The first step is to place the carbide slag in a calcining furnace for low-temperature calcination; In the second step, the calcined carbide slag is slurried with water to form a slurry with a solid content of 10%-20%, and then 3%-10% of the total mass of the slurry is added to the slurry with a particle size of 2-100μm. 4 or CaSO 4 1 / 2H 2 O, let stand for 15-45 minutes; The third step is to pass the slurry after standing into a strong magnetic separator for wet magnetic separation; The fourth step is to discharge the carbide slag slurry after magnetic separation into a sedimentation tank for sedimentation. The sedimentation time is 4-48 hours. The slurry is divided into a supernatant layer and a solid sedimentation layer by sedimentation. The lower 0-1 / 3 of the solid sedimentation layer is the solid sedimentation lower layer, and the upper 1 / 3-1 of the solid sedimentation layer is the solid sedimentation upper layer. In the fifth step, the solid sedimentation upper layer of the carbide slag slurry and the supernatant are introduced into a carbonization reactor, and a mixture of sodium tripolyphosphate (1%-3% by weight of the carbide slag) and EDTA (1%-3% by weight of the carbide slag) is added as a crystal form regulator, and CO (30%-95%) is introduced while stirring. 2 Gas, based on kg of carbide slag, is fed with a flow rate of 10 L / min of CO 2 When the pH of the slurry is 6-6.5, stop introducing CO 2 ; The sixth step is to filter the mineralized slurry to obtain a filter cake, and then dry and grind the filter cake to obtain a nano calcium carbonate product.

[0008] Furthermore, in the first step, the calcination temperature is 200-550° C., and the calcination time is 2-5 hours.

[0009] Furthermore, the magnetic field intensity during the magnetic separation in the third step is 1.0T-2.5T, and the magnetic separation time is 1-3h.

[0010] Furthermore, the filtering method in the sixth step includes any one of vacuum filtration, centrifugal filtration, and pressure filtration; the drying method includes any one of heating drying, vacuum drying, and conveyor belt drying, the drying temperature is 75-150°C, and the drying time is 3-6h.

[0011] According to the physical and chemical properties of carbide slag, the present invention uses low-temperature calcination to remove moisture and organic impurities in carbide slag; for Fe-based magnetic impurities in carbide slag, wet magnetic separation is used to remove them. In particular, for impurities SiO 2 The separation is carried out by combining mineral characteristics with gravity separation, that is, adding CaSO with a particle size of 2-100 μm to the carbide slag slurry. 4 Granular, larger particle size CaSO 4 The particles will preferentially form on SiO 2 surface growth and wrapping, while CaSO 4 The density is 2.96 g / cm 3 , Ca(OH) 2 Density is about 2.24g / cm 3 The two can be separated by sedimentation method, thus removing SiO2 from carbide slag. 2Finally, the mineralization reaction process is introduced to obtain a high-purity nano calcium carbonate product. The characteristic of this method is that the energy consumption of the process is greatly reduced through low-temperature calcination, and at the same time, the method of combining mineral characteristics with gravity separation is introduced to remove SiO 2 , which solves the problems of high energy consumption and difficulty in removing impurities in the carbide slag treatment process.

[0012] The beneficial effects of the present invention are as follows: Compared with the process of high-temperature calcination of carbide slag, this process uses low-temperature calcination of carbide slag, which can not only remove coke and moisture from it, but also greatly reduce energy consumption. 4 Encapsulated SiO 2 Impurities. Finally, a calcium carbonate product with a purity of 95.00%-99.60% and a whiteness of 95.0-98.0 is obtained. The process method of the present invention is easy to operate and plays a role in improving efficiency in production; it can achieve efficient separation of impurities and increase the added value of the production process. In summary, the process of the present invention is simple, and has obvious energy-saving advantages and strong practicality. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 For the present invention, CO 2 Flow chart of producing high-purity nanocarbonic acid from mineralized carbide slag. DETAILED DESCRIPTION

[0014] In order to make the objects and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0015] Example 1 A method of utilizing CO 2 The method for producing high-purity nano calcium carbonate from mineralized carbide slag comprises the following steps: a) Place the carbide slag in a calcining furnace and calcine it at a low temperature of 200°C for 2 hours; b) Add water to the calcined carbide slag to form a slurry with a solid content of 10%, and then add 3% of the total weight of the slurry CaSO with a particle size of 2-80μm to the slurry. 4 or CaSO 4 1 / 2H 2 O, let stand for 15 minutes; c) passing the slurry after standing into a strong magnetic separator for wet magnetic separation, the magnetic field intensity during magnetic separation is 1.0T, and the magnetic separation time is 1h; d) The carbide slag slurry after magnetic separation is discharged into a sedimentation tank for sedimentation. The sedimentation time is 4 hours. The slurry is divided into a supernatant layer and a solid sedimentation layer by sedimentation. The lower 1 / 6 of the solid sedimentation layer is the solid sedimentation lower layer, and the upper 1 / 3 of the solid sedimentation layer is the solid sedimentation upper layer; e) The solid sedimentation upper layer of the carbide slag slurry and the supernatant are introduced into the mineralization reactor, and a mixture of 1% sodium tripolyphosphate and 1% EDTA by mass of the carbide slag is added as a crystal form regulator, and a CO content of 30% is introduced while stirring. 2 Gas, based on kg of carbide slag, a flow rate of 10L / min of CO 2 When the pH of the slurry reaches 6.5, stop introducing CO 2 ; f) Filtering the mineralized slurry to obtain a filter cake, and drying and grinding the filter cake to obtain a nano calcium carbonate product.

[0016] The filtering method in the above step f) is vacuum filtration; the drying method is vacuum drying, the drying temperature is 75° C., and the drying time is 3 hours.

[0017] In this case, the mineralization reaction time of 500 kg of carbide slag was 1 hour, and the mass of the obtained nano calcium carbonate product was 486.5 kg, the purity reached 95.0%, and the whiteness reached 95.0%.

[0018] Example 2 The method and workflow are the same as those in Example 1, except that: a) Place the carbide slag in a calcining furnace and calcine it at a low temperature of 550°C for 5 hours; b) The calcined carbide slag is slurried with water to form a slurry with a solid content of 20%, and then 10% of the total mass of the slurry is added with CaSO with a particle size of 40-100 μm. 4 or CaSO 4 1 / 2H 2 O, let stand for 45 minutes; c) passing the slurry after standing into a strong magnetic separator for wet magnetic separation, the magnetic field intensity during magnetic separation is 2.5T, and the magnetic separation time is 5h; d) The carbide slag slurry after magnetic separation is discharged into a sedimentation tank for sedimentation. The sedimentation time is 48 hours. The slurry is divided into a supernatant layer and a solid sedimentation layer by sedimentation. The lower 1 / 3 of the solid sedimentation layer is a solid sedimentation lower layer, and the upper 2 / 3 of the solid sedimentation layer is a solid sedimentation upper layer; e) The solid sedimentation upper layer of the carbide slag slurry and the supernatant are introduced into a mineralization reactor, a mixture of 3% sodium tripolyphosphate and 3% EDTA by mass of the carbide slag is added as a crystal form regulator, and a CO content of 95% is introduced while stirring. 2Gas, with a flow rate of 10L / min of CO per ton of carbide slag 2 When the pH of the slurry reaches 6.5, stop introducing CO 2 ; f) Filtering the mineralized slurry to obtain a filter cake, and drying and grinding the filter cake to obtain a nano calcium carbonate product.

[0019] The filtering method in the above step f) is centrifugal filtration; the drying method is heating drying, the drying temperature is 150° C., and the drying time is 6 hours.

[0020] In this case, the mineralization reaction time of 500 kg of carbide slag was 1 hour, and the mass of the obtained nano calcium carbonate product was 475.35 kg, the purity reached 96.3%, and the whiteness reached 96.5%.

[0021] Example 3 The method and workflow are the same as those in Example 1, except that the steps a) Place the carbide slag in a calcining furnace and calcine it at a low temperature of 450°C for 3.5 hours; b) Add water to the calcined carbide slag to form a slurry with a solid content of 15%, and then add 5% of the total mass of the slurry CaSO with a particle size of 10-50μm to the slurry. 4 or CaSO 4 1 / 2H 2 O, let stand for 30 minutes; c) passing the slurry after standing into a strong magnetic separator for wet magnetic separation, the magnetic field intensity during magnetic separation is 2.0T, and the magnetic separation time is 2.5h; d) The carbide slag slurry after magnetic separation is discharged into a sedimentation tank for sedimentation. The sedimentation time is 24 hours. The slurry is divided into a supernatant layer and a solid sedimentation layer by sedimentation. The lower 1 / 3 of the solid sedimentation layer is the solid sedimentation lower layer, and the upper 1 / 6 of the solid sedimentation layer is the solid sedimentation upper layer; e) The solid sedimentation upper layer of the carbide slag slurry and the supernatant are introduced into a mineralization reactor, a mixture of 3% sodium tripolyphosphate and 1% EDTA by mass of the carbide slag is added as a crystal form regulator, and a CO content of 95% is introduced while stirring. 2 Gas, with a flow rate of 10L / min of CO per ton of carbide slag 2 When the pH of the slurry reaches 6.5, stop introducing CO 2 ; f) Filtering the mineralized slurry to obtain a filter cake, and drying and grinding the filter cake to obtain a nano calcium carbonate product.

[0022] The filtering method in the above step f) is pressure filtration; the drying method is vacuum drying, the drying temperature is 105° C., and the drying time is 4 hours.

[0023] In this case, the mineralization reaction time of 500 kg of carbide slag was 1 hour, and the mass of the obtained nano calcium carbonate product was 432.5 kg, the purity reached 99.6%, and the whiteness reached 98.0%.

[0024] Example 4 The method and workflow are the same as those in Example 1, except that: a) Calcine the carbide slag in a calcining furnace at a low temperature of 300°C for 3.5 hours; b) The calcined carbide slag is mixed with water to form a slurry with a solid content of 19%, and then 9% of the total mass of the slurry is added to the slurry with a particle size of 2-70 μm. 4 or CaSO 4 1 / 2H 2 O, let stand for 25 minutes; c) passing the slurry after standing into a strong magnetic separator for wet magnetic separation, the magnetic field intensity during magnetic separation is 1.5T, and the magnetic separation time is 2h; d) The carbide slag slurry after magnetic separation is discharged into a sedimentation tank for sedimentation. The sedimentation time is 37 hours. The slurry is divided into a supernatant layer and a solid sedimentation layer by sedimentation. The lower 1 / 6 of the solid sedimentation layer is the solid sedimentation lower layer, and the upper 2 / 3 of the solid sedimentation layer is the solid sedimentation upper layer; e) The solid sedimentation upper layer of the carbide slag slurry and the supernatant are introduced into a mineralization reactor, a mixture of 2% sodium tripolyphosphate and 2% EDTA by mass of the carbide slag is added as a crystal form regulator, and a CO content of 60% is introduced while stirring. 2 Gas, with a flow rate of 10L / min of CO per ton of carbide slag 2 When the pH of the slurry reaches 6, stop introducing CO 2 ; f) Filtering the mineralized slurry to obtain a filter cake, and drying and grinding the filter cake to obtain a nano calcium carbonate product.

[0025] The filtering method in the above step f) is vacuum filtration; the drying method is conveyor belt drying, the drying temperature is 145° C., and the drying time is 5 hours.

[0026] In this case, the mineralization reaction time of 500 kg of carbide slag was 1 hour, and the mass of the obtained nano calcium carbonate product was 457.9 kg, the purity reached 97.8%, and the whiteness reached 97.2%.

[0027] Example 5 The method and workflow are the same as in Example 1, except that: a) Place the carbide slag in a calcining furnace and calcine it at a low temperature of 200°C for 2 hours; b) The calcined carbide slag is slurried with water to form a slurry with a solid content of 17%, and then CaSO with a particle size of 2-100 μm is added to the slurry at a concentration of 7% of the total mass of the slurry. 4 or CaSO 4 1 / 2H 2 O, let stand for 45 minutes; c) passing the slurry after standing into a strong magnetic separator for wet magnetic separation, the magnetic field intensity during magnetic separation is 1.8T, and the magnetic separation time is 2.0h; d) The carbide slag slurry after magnetic separation is discharged into a sedimentation tank for sedimentation. The sedimentation time is 15 hours. The slurry is divided into a supernatant layer and a solid sedimentation layer by sedimentation. The lower 1 / 6 of the solid sedimentation layer is the solid sedimentation lower layer, and the upper 2 / 3 of the solid sedimentation layer is the solid sedimentation upper layer; e) The solid sedimentation upper layer of the carbide slag slurry and the supernatant are introduced into a mineralization reactor, a mixture of 3% sodium tripolyphosphate and 3% EDTA by mass of the carbide slag is added as a crystal form regulator, and a mixture of 50% CO is introduced while stirring. 2 Gas, with a flow rate of 10L / min of CO per ton of carbide slag 2 When the pH of the slurry reaches 6.5, stop introducing CO 2 ; f) Filtering the mineralized slurry to obtain a filter cake, and drying and grinding the filter cake to obtain a nano calcium carbonate product.

[0028] The filtering method in the above step f) is pressure filtration; the drying method is vacuum drying, the drying temperature is 105° C., and the drying time is 4.5 hours.

[0029] In this case, the mineralization reaction time of 500 kg of carbide slag was 1 hour, and the mass of the obtained nano calcium carbonate product was 470.15 kg, the purity reached 97.3%, and the whiteness reached 96.5%.

Claims

1. A method for producing high-purity nano calcium carbonate using CO2 mineralized carbide slag, characterized in that: The steps include: The first step is to place the carbide slag in a calcining furnace for low-temperature calcination; The second step is to add water to the calcined carbide slag to form a slurry with a solid content of 10%-20%, and then add 3%-10% of the total mass of the slurry CaSO4 or CaSO4·1 / 2H2O with a particle size of 2-100μm to the slurry, and let it stand for 15-45 minutes; The third step is to pass the slurry after standing into a strong magnetic separator for wet magnetic separation; The fourth step is to discharge the carbide slag slurry after magnetic separation into a sedimentation tank for sedimentation. The sedimentation time is 4-48 hours. The slurry is divided into a supernatant layer and a solid sedimentation layer by sedimentation. The lower 0-1 / 3 of the solid sedimentation layer is the solid sedimentation lower layer, and the upper 1 / 3-1 of the solid sedimentation layer is the solid sedimentation upper layer. The fifth step is to introduce the solid sedimentation upper layer and the supernatant of the carbide slag slurry into a carbonization reactor, add a mixture of sodium tripolyphosphate (1%-3% by weight of the carbide slag) and EDTA (1%-3% by weight of the carbide slag) as a crystal form regulator, stir and introduce CO2 gas with a content of 30%-95%, and introduce CO2 gas at a flow rate of 10L / min per kilogram of carbide slag until the slurry pH is 6-6.5 and stop introducing CO2; The sixth step is to filter the mineralized slurry to obtain a filter cake, and then dry and grind the filter cake to obtain a nano calcium carbonate product.

2. A method for producing high-purity nano calcium carbonate by utilizing CO2 mineralized carbide slag according to claim 1, characterized in that: In the first step, the calcination temperature is 200-550° C., and the calcination time is 2-5 hours.

3. A method for producing high-purity nano calcium carbonate by utilizing CO2 mineralized carbide slag according to claim 1, characterized in that: The magnetic field intensity during the magnetic separation in the third step is 1.0T-2.5T, and the magnetic separation time is 1-3h.

4. A method for producing high-purity nano calcium carbonate by utilizing CO2 mineralized carbide slag according to claim 1, characterized in that: The filtering method in the sixth step includes any one of vacuum filtration, centrifugal filtration, and pressure filtration; the drying method includes any one of heating drying, vacuum drying, and conveyor belt drying, the drying temperature is 75-150°C, and the drying time is 3-6h.